Sharia-Oriented Performance of Local Government-Owned Islamic Rural Banks in Indonesia: A Disclosure-Based Descriptive Assessment Using the Islamicity Performance Index - Nirwan Umasugi; Syaifuddin Syaifuddin; Rusmiyanti Wontami; Abd Rauf Wajo; Muhammad Ufuqul Mubin (Al-Qalam Institute, 2026)
This study evaluates the sharia-oriented financial performance of local government-owned Islamic rural banks (BPRS) in Indonesia using a disclosure-based Islamicity Performance Index (IPI). The sample comprises 21 BPRS observed during the 2024 financial year. A cross-sectional quantitative descriptive approach was applied by calculating bank-level ratios and reporting descriptive statistics without hypothesis testing or econometric estimation. Six indicators were examined: profit-sharing distribution, Zakat Performing Ratio, equitable distribution, employee-to-director welfare, Islamic Investment Ratio, and Islamic Income Ratio. Proxy construction and missing-data treatment were explicitly specified because public reports did not consistently disclose all canonical IPI components. The available profit-sharing proxy (n = 14) averaged 9.21%, while the Zakat Performing Ratio, equitable-distribution proxy, and employee-to-director welfare ratio averaged 0.099%, 28.10%, and 26.34%, respectively. Following standardization, Islamic investments accounted for 99.823% of total investments, while Islamic income accounted for 99.976% of total income. The findings demonstrate consistently strong alignment in investment and income sources but greater variation in profit-sharing, zakat, and distributive outcomes. OJK, PERMABIDA, local government shareholders, and BPRS management should therefore establish standardized IPI disclosure fields and institution-specific social performance targets to strengthen comparability, accountability, and policy oversight.